Professional Development of Mobilizer Teachers Through a Coaching Lesson Study Approach (Design Principles and Its Applications Merdeka Learn/Merdeka Teaches Edition) - Widodo Widodo; Agus Wahyudin; Masrukhi Masrukhi; Widiyanto Widiyanto (International Conference on Science, Education, and Technology, 2023)
The idea of teacher professional development is the most phenomenal topic because it demands innovative practices to improve didactical-pedagogical skills. In line with the Implementation of the Merdeka Curriculum (IKM) and Teacher Mobilization Education Program, although this author's idea is a modification, it emphasizes proposals that focus on strengthening teachers, that encourage reflection and collaboration among teachers, and that promote an academic approach to learning. Coaching Lesson Study (CLS) is a solution to answer these demands and what is known as the Collaboration of Teaching and Learning. CLS is a cyclical process in which a group of teachers collaborated in designing, teaching, observing, and discussing lessons that are, in parallel, being investigated to improve them. In doing so, CLS links teacher professional development to student learning, integrates coaching and teaching practice, and facilitates self-inspection through observation and reflection among peers. This article presents seven principles for practicing CLS as an innovative idea for teacher professional development that is based on what the literature suggests and on best practice in education and learning. In many studies CLS contributes to the development of teacher's didactic knowledge but if it is collaborated with Coaching techniques, the results should be more optimal.